Application evaluation and promotion effect of normal pressure shale gas demonstration well in Nanchuan area in southeastern Chongqing - Yunhai WANG; Qing HE; Zhichao ZHU; Zhiping LONG; Xing PENG; Jianshan CAO (Shiyou shiyan dizhi, 2023)
Nanchuan area in southeastern Chongqing is rich in normal pressure shale gas resources, which is an important area for SINOPEC's shale gas exploration and development. Due to the complex geological conditions and imperfect engineering technology, the overall efficiency of drilling acceleration and efficiency improvement in this area can not meet the requirements for large-scale benefit-based development of normal pressure shale gas. Therefore, Yangye 54-3HF well in Yangchungou block in this area is selected as the first normal pressure shale gas demonstration well of SINOPEC to research and form a regional optimal and fast drilling and completion demonstration technology series. On the basis of systematic analysis of regional drilling technology difficulties, combined with basic research on formation pressure resistance characteristics and formation pressure system, the demonstration well research systematically explores key drilling technologies such as shallow formation leakage technology, well structure optimization technology, accelerating tool optimization technology, trajectory control and orientation technology, low-density strong plugging oil-based drilling fluid technology, and optimal fast completion technology. A low-cost, optimal, and fast drilling demonstration technology system with the core of shallow formation prospecting, large-capacity clean water drilling, optimized well structure, domestic acceleration tools, low-density and strong plugging oil-based drilling fluid, integrated geological engineering orientation, and low-pressure wellbore fast cementing technology is formed. The drilling period of the demonstration well is 19.96 d, which is the shortest drilling period in 4 500 m well depth in China, and the ROP is 24.88 m/h, which is 141.79% higher than the fastest ROP of 10.29 m/h in the similar well depth in the same region. The rate of drilling in high-quality shale is 100%, and the cementing quality is excellent, which has played a good demonstration and leading role. After the promotion and application, various technical and economic indicators such as the regional ROP and drilling period have been significantly improved, speeding up the exploration and development process of normal pressure shale gas in Nanchuan area. The practice of normal pressure shale gas demonstration wells in Nanchuan area has shown that the efficient drilling and completion technology series formed by the demonstration well research can meet the requirements of drilling acceleration and efficiency improvement in horizontal wells of normal pressure shale gas, effectively promoting the four improvements in petroleum engineering to a new level, and laying a technical foundation for the construction of similar gas fields around the Sichuan Basin, and helping achieve greater progress in stabilizing oil and gas production, reducing costs, and improving efficiency in the upstream industry in China.